EFEKTIVITAS MODEL PEMBELAJARAN CORE TERHADAP MINAT BELAJAR PAI PESERTA DIDIK - Endhah Tryadumawati; Jamal Fakhri; Muhammad Mustofa (Jurnal Bilqolam Pendidikan Islam, 2026)
This study aims to examine the effectiveness of the CORE (Connecting, Organizing, Reflecting, and Extending) learning model in enhancing students' interest in learning Islamic Religious Education (IRE) at SMP Negeri 37 Bandar Lampung. The study was motivated by students' low interest in learning, as indicated by limited classroom engagement, low participation, and the predominance of conventional teaching methods. This study employed a quantitative approach using a quasi-experimental method with a Posttest-Only Control Group Design. The research sample consisted of an experimental class that implemented the CORE learning model and a control class that received conventional instruction. Data were collected using a learning interest questionnaire that had met the required validity and reliability criteria and were subsequently analyzed through normality and homogeneity tests, followed by an Independent Samples t-test. The findings revealed a statistically significant difference in learning interest between students in the experimental and control groups. These results indicate that the CORE learning model is effective in improving students' interest in learning Islamic Religious Education, particularly in terms of learning enthusiasm, the habit of reviewing learning materials, and active participation through questioning and classroom engagement. This study highlights the potential of the CORE learning model as an innovative instructional approach to fostering students' learning interest in Islamic Religious Education at the junior secondary school level.